Cost effectiveness analysis of subcutaneous low molecular weight heparin compared to intravenous unfractionated heparin in the shortern management of unstable angina - Punzalan, Felix Eduardo
Background: There are high costs associated with management of unstable angina. Patients are hospitalized for treatment and close monitoring to prevent complications and death. Intravenous unfractionated heparin and aspirin are proven to reduce cardiac events in these cases. Recent trials have shown that low molecular weight heparin is also effective. It has a more stable anticoagulant effect allowing subcutaneous dosing without need for laboratory monitoring unlike unfractionated heparin which requires infusion and titration based on activated partial thromboplastin time to achieve therapeutic dose. However, while it is more convenient to administer, the drug is more expensive in terms of unit cost. An economic evaluation is relevant to determine whether low molecular weight heparin is more cost effective compared to unfractionated heparin in the management of unstable angina. Objective: To determine the cost effectiveness of low molecular weight heparin compared to intravenous unfractionated heparin in the short-term management of unstable angina from a societal viewpoint. Design: Cost effectiveness analysis. Study Sample and Setting: Forty-five patients with unstable angina included in a randomized controlled trial conducted at the Philippine Heart Center for Asia in 1999 comparing low molecular weight heparin nadroparin and intravenous unfractionated heparin. Methods: Cost of resource use and clinical course within the 7-day treatment were assessed through evaluation of patient case report forms and hospital records, correspondence with the trial investigators, conduct of surveys, interviews and actual observation. The effectiveness estimate was based on the metaanalysis by Eikelboom, et al. 2000, which compared low molecular weight heparin and unfractionated intravenous heparin in unstable angina in the reduction of clinical outcomes. Cost effectiveness ratio was determined. Sensitivity analysis evaluated the effect of variation of cost and effectiveness data of low molecular weight heparin based on the upper and lower boundaries of the interval estimates of the cost effectiveness ratio. We also estimated the effect of excluding indirect medical cost and of using different discount rates from the overall cost of treatment. Results: The mean cost for the subcutaneous low molecular weight heparin nadroparin group was PhP (Philippine Pesos) 16,635.68 and for the intravenous unfractionated heparin group was Ph 17,972.01 with a mean difference of (-) PhP 1,336.33 [95%CI : (-) 5,631.87 ? 2959.20]. After controlling for all the variables except for the low molecular weight heparin treatment on multiple regression analysis, the cost difference was (-) 1654.16, 95% CI: (-)6567 ? 3259.04, consistent with the primary analysis. The costs of intensive care unit stay, activated partial thromboplastin time determinations, and cost of supplies, use of infusion pump, and nursing time for heparin administration were significantly higher with the intravenous unfractionated heparin (UFH) group. In terms of benefit, subcutaneous low molecular weight heparin could confer 5.1% [95%CI: 0- 9.2] absolute risk reduction of recurrent angina. Therefore, based on the point estimate, low molecular weight therapy could realize a cost saving of PhP 1,336.33 and 5.1% absolute reduction in the risk of recurrent angina. PhP 26,202.55 can be saved for every case of recurrent angina prevented. Based on the boundaries of the confidence intervals, low molecular weight heparin therapy will afford cost saving of as much as PhP 5,631.87 while reducing risk of recurrent angina by 9.2%, on the other end, there could be an additional cost of P2959.20 while achieving similar clinical benefit with unfractionated heparin. Among patients given intravenous unfractionated heparin, 54.5% failed to achieve therapeutic dose. This further favors the use of low molecular weight heparin to assure achievement of therapeutic effect while obviating the complexity of unfractionated heparin administration. There were no major bleeding episodes noted while the incidence rates of minor bleeding were similar in both groups. Sensitivity analysis varying discount rates and excluding indirect cost did not affect the results. Conclusions: From a societal perspective, the mean cost of 7 day therapy for unstable angina is PhP 16,635.68 with subcutaneous low molecular weight heparin compared to PhP 17,972.01 with intravenous unfractionated heparin therapy. Among patients with unstable angina, low molecular weight heparin compared with intravenous unfractionated heparin therapy could achieve 5.1% reduction in recurrent angina. The cost effectiveness ratio showed that subcutaneous low molecular weight heparin could achieved a cost saving of PhP 1,336.33 while reducing the risk of recurrent angina by 5.1%, corresponding to PhP 26,202.55 saved for every case of recurrent angina prevented. At best, there could be a cost saving of PhP 5,631.87 and 9.2% risk reduction of recurrent angina and at worst, an additional expense of PhP 2,959.20 while achieving the same benefit as unfractionated heparin. There were few minor bleeding episodes and the incidence rates are similar between the two treatment groups. Considering the potential cost saving, its practical advantages, safety profile, reduction in recurrent angina and the low rate of achieving therapeutic levels with intravenous unfractionated heparin, low molecular weight heparin may be preferred over unfractionated heparin in the short term management of unstable angina.
Theses--(MS in Epidemiology-Clinical Epidemiology) University of the Philippines Manila
Keywords: Heparin; Cost and cost analysis